(untitled) (Marketing Journal, 2025)
This article discusses the theoretical foundations of the concept of state economic security, its formation factors and main indicators. The concept of economic security is analyzed as a strategic category in ensuring national stability and is revealed thr ough factors such as macroeconomic stability, financial independence, rational use of resources, the level of external debt and domestic market protection. The article 324 compares various theoretical approaches (based on classical, institutional and modern macroeconomic models), and also summarizes methods for assessing economic security from a theoretical point of view. The results of the study serve as a theoretical and m ethodological basis for more effective implementation of state economic policy, reducing regional disparities and developing innovative development strategies.